2010
DOI: 10.1111/j.1365-2966.2010.16313.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical turbulence vertical distribution with standard and high resolution at Mt Graham

Abstract: A characterization of the optical turbulence vertical distribution (C2N profiles) and all the main integrated astroclimatic parameters derived from the C2N and the wind speed profiles above the site of the Large Binocular Telescope (LBT) (Mt Graham, Arizona, USA) is presented. The statistics include measurements related to 43 nights done with a Generalized SCIDAR (GS) used in standard configuration with a vertical resolution ΔH∼ 1 km on the whole 20 km and with the new technique (High Vertical Resolution GS) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This result is consistent with turbulence distributions obtained by Masciadri et al [6] on nearby Mount Graham, Arizona. Preliminary results using the same high vertical resolution generalized-SCIDAR approach, proposed by Egner et al [7], showed a similar concentration of turbulence near the ground.…”
Section: Estimation Of Mmt Glao Performancesupporting
confidence: 94%
“…This result is consistent with turbulence distributions obtained by Masciadri et al [6] on nearby Mount Graham, Arizona. Preliminary results using the same high vertical resolution generalized-SCIDAR approach, proposed by Egner et al [7], showed a similar concentration of turbulence near the ground.…”
Section: Estimation Of Mmt Glao Performancesupporting
confidence: 94%
“… We consider it extremely important to take into consideration the atmospheric data of the different sites in order to improve the adaptive optics systems by using the different atmospheric turbulence profiles. In this way, the systems would be calibrated according to the sky in which they operate [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Control applications also should be developed taking into account the particularities of each telescope and environment where it is currently operating.…”
Section: Discussionmentioning
confidence: 99%
“…Also on the seeing point of view, Mount Graham has shown a behavior remarkably good (see [26] e [20]), with an average estimated seeing of about 1" achieved during the commissioning of FLAO and, furthermore, with several nights in which the seeing has been lower than 0.8" and sometimes as good as 0.3" in V Band.…”
Section: Introductionmentioning
confidence: 87%